THE LANGUAGE ATTITUDE OF FOLLOWERS TOWARDS DIAN PELANGI USING CODE SWITCHING IN HER INSTAGRAM - NUR OKSIALVIYANTI, ESA (LANGUAGE HORIZON, 2018)
Code switching is phenomenon which occurs in bilingual country,such us,Indonesia. Code switching is the process of switching or mixing two languages or more with in or between sentence. Most of researchers analyze code switching in oral text. So, this study used written text to be analyzed, specially in Computer Mediated Communication (CMC). CMC is the communication between human by computer. This study used Instagram of DianPelangi who is famous designer. This study focused on her caption which is categorized asasynchronous CMC. The aim of this study is to uncover the reactions of her followers towards code switching in her caption. Questionnaire was the technique to collect the data. The results of this study revealed that most of the participants assumed that the use of code switching by Dian Pelangi is positive. However, the half of participants prefer if she employed only one language while writing caption. Keywords: language attitude, code switching, Instagram